Moderating effect of psychological empowerment on relationship between leadership style and innovative work behavior - Md Khan, Arif (2019)
Special attention has been devoted to the relationship between leadership style and innovative work behavior (IWB) over the past years. There is an abundant literature on that the leadership style which effect on innovative work behavior (IWB), however, the evidence corroborating the link between transformational leadership (TFL), transactional leadership (TNL) and innovative work behavior (IWB) has been lacking, especially in the banking sector in Bangladesh. Given this deficiency, this study investigates the effects of transformational leadership (TFL) and transactional leadership (TNL) on innovative work behavior (IWB), especially the employees in commercial banks in Bangladesh. In addition, the moderating effect of psychological empowerment on these relationships is examined. Based on the quantitative technique, the study used SPSS and Smart-PLS for analysis on 372 of sample data collected from employees in the commercial banks of Bangladesh. The findings show that innovative work behavior (IWB) is positively and negatively related to transformational leadership (TFL) and transactional leadership (TNL) respectively. Interestingly, the impact of transformational leadership (TFL) on innovative work behavior (IWB) is more pronounced when psychological empowerment (PE) of employees is high, whereas the effect of transactional leadership (TNL) becomes negative under these circumstances. The implication of this study is mainly derived from understanding of psychological empowerment (PE) at individual level of employees and its effect on innovative work behavior (IWB) with the use of both transformational leadership (TFL) and transactional leadership (TNL) style. Therefore, it is crucial for the leaders to combine these practices in their behavior. There is also a need to understand the fact of individual level psychological empowerment in order to foster employees innovative work behavior (IWB). Future research could be conducted by exploring the practices which are most relevant to innovative work behavior (IWB) of employees, relating to contingency factors which influence the connection of Transformational leadership (TFL), transactional leadership (TNL) and innovative work behavior (IWB).